Preparation and evaluation of some eco-friendly olethio-amide derivatives as lube oil additives - Rasha S. Kamal; Entsar E. Badr; Ibrahim M. Nassar; Nour E.A. AbdEl-Sattar (Egyptian Journal of Petroleum)
Eco-friendly synthesis of organic compounds is a major trend in green chemistry. Thus, we aim at producing some of the lube oil additives through the use of green chemistry. Dispersant lube oil additives are remarkable additives that regulate the formation of deposits throughout the process. Antioxidants do not prevent the oxidation reactions but only delay the rate of this process. In the present work, some additives for lube oil based on thiourea derivative were prepared by one-step reaction, which is the reaction of octadeca-7-enoy) chloride with ammonium thiocyanate in addition to different amines such as ethylenediamine, diethylene triamine, and tetraethylene pentamine as three-component system in order to prepare thioamide derivatives (A, B, and C). Infrared spectroscopy, elemental analysis, nuclear magnetic resonance, determination of molecular weights, and yield determination verified the chemical structure of all synthesized molecules. All the compounds produced are tested as lube oil additives (dispersants and antioxidants), and it has been found that all the compounds prepared are good as dispersants but have poor effect as antioxidants. The theoretical result is the same as the experimental result of antioxidants through the use of the quantum chemical calculations by calculating the energy gap (EHOMO-ELUMO). The best dispersant lube oil additive is (C).